Optimizing Solar Power Plant Efficiency: Advancements in Hot Area Cooling Systems - Mariscal Gonzalez, Ana (My University, 2025)
Solar energy has become a widely adopted and sustainable alternative for power generation. However, solar panels, present performance limitations such as the de- crease on performance when its working temperature exceeds 25°C [1]. This issue is especially pronounced in regions near the equator, where high solar exposure that leads to more energy production, is accompanied by elevated ambient temperatures that cause thermal stress on Photovoltaic (PV) systems and reducing their overall effectiveness. This study addresses the performance limitations of solar panels in hot climates by evaluating an active cooling system designed to reduce panel tem- peratures and improve efficiency. A three-year experimental analysis (2022–2024) was conducted in Southwest Finland on three solar panel arrays. In the final year, a cooling system—comprising a network of coolant-carrying pipes—was installed under one array, and its performance was compared across the summer months (July–September) of each year. Additionally, a computational model replicating the cooling setup was developed, incorporating variables such as geographic location, so- lar position, irradiation, and ambient temperature. The model was further applied to simulate conditions in the Tabernas Desert in Spain to assess its effectiveness in hotter climates. It also explored system optimization by adjusting design parame- ters and environmental inputs, offering a versatile tool for adapting cooling systems to various geographical settings.
Keywords: Solar panel, active cooling, computational model.